Genetic basis of inter-individual variability in the effects of exercise on the alleviation of lifestyle-related diseases - Mori, Masayuki (Blackwell Science Inc, 2009)
Habitual exercise training, including a high-intensity interval walking programme, improves cardiorespiratory fitness and alleviates lifestyle-related diseases, such as obesity, hypertension and dyslipidaemia. However, the extent of improvement has been shown to differ substantially among individuals for various exercise regimens. A body of literature has demonstrated that gene polymorphisms could account for the inter-individual variability in the improvement of risk factors for lifestyle-related diseases following exercise training. However, the fractions of the variability explained by the polymorphisms are small (∼5%). Also, it is likely that the effects of gene polymorphisms differ with exercise regimens and subject characteristics. These observations suggest the necessity for further studies to exhaustively identify such gene polymorphisms. More importantly, the physiological and molecular genetic mechanisms by which gene polymorphisms interact with exercise to influence the improvements of risk factors for lifestyle-related diseases differentially remain to be clarified. A better understanding of these issues should lead to more effective integration of exercise to optimize the treatment and management of individuals with lifestyle-related diseases.